Formulasi Sediaan Patch Bioselulosa Ekstrak Daun Kelor (Moringa oleifera) untuk Pengobatan Luka Bakar: Formulation of Moringa Leaf (Moringa oleifera) Extract Biocellulose Patch for Burns Treatment - Susanti, Susanti; Fadilah, Nitya Nurul; Nurani, Ai Selvia; Karimah, Ira Siti; Wulandari, Nita; Dani, Rendi Saepul (Jurnal Sains dan Kesehatan, 2024)
The large number of problems and incidents of burn wounds has encouraged researchers to study pharmaceutical products for burn wounds, one of which is modified patch with biocellulose-based materials which have the ability to maintain a moist environment in the wound and absorb exudates during the inflammatory phase. To further increase the effectiveness of healing burns, biocellulose patches can also be fortified with natural ingredients, one of which is Moringa oleifera leaves. Moringa leaves contain saponin which is a compound that stimulates the formation of collagen, a structural protein that plays a role in the wound healing process and also has the ability to act as a cleanser so it is effective for healing open wounds. The aim of this research was to formulate a biocellulose patch fortified with Moringa leaf extract and test its burn wound healing activity. The patch is made from nata by fermenting coconut water using Acetobacter xylinum, then the patch is fortified with Moringa leaf extract in 3 concentrations (F1=3%, F2=6%, F3=9%). Evaluations carried out include organoleptic tests, pH, uniformity of size and thickness. The effectiveness test for healing burn wounds was carried out on experimental mice. All patch meet the physical evaluation test requirements. The patch in F3 had a burn wound healing percentage that was close to the positive control, namely 92.91% on the 8th day. Keywords:          biocellulose, moringa, burns, patch   Abstrak Banyaknya masalah dan kejadian luka bakar memacu peneliti dalam mengkaji sediaan farmasi untuk luka bakar tersebut salah satunya modifikasi sediaan patch dengan bahan dasar bioselulosa yang memiliki kemampuan untuk mempertahankan lingkungan yang lembab pada luka dan menyerap eksudat selama fase inflamasi. Dalam upaya meningkatkan efektivitas penyembuhan luka bakar, patch bioselulosa juga dapat difortifikasi dengan bahan alam salah satunya yaitu daun kelor (Moringa oleifera). Daun kelor memiliki kandungan saponin yang merupakan salah satu senyawa yang memacu pembentukan kolagen, yaitu protein struktur yang berperan dalam proses penyembuhan luka sekaligus mempunyai kemampuan sebagai pembersih sehingga efektif untuk penyembuhan luka terbuka. Tujuan penelitian ini adalah untuk memformulasikan sediaan patch bioselulosa yang difortifikasi ekstrak daun kelor dan menguji aktivitas penyembuhan luka bakarnya. Sediaan patch dibuat dari nata dengan cara fermentasi air kelapa menggunakan bakteri Acetobacter xylinum kemudian patch difortifikasi ekstrak daun kelor dalam 3 konsentrasi (F1=3%, F2=6%, dan F3=9%). Evaluasi yang dilakukan diantaranya uji organoleptis, pH, keseragaman ukuran dan ketebalan. Uji efektivitas penyembuhan luka bakar dilakukan terhadap tikus percobaan. Semua sediaan patch memenuhi syarat uji evaluasi fisik. Sediaan pada F3 memiliki persentase penyembuhan luka bakar yang mendekati kontrol positif yaitu sebesar 92,91% pada hari ke-8. Kata Kunci:         bioselulosa, kelor, luka bakar, patch